Chad : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, Chad's economic developments and policies have been prepared by an IMF staff team. The recent economic developments and risks of the financial system are reported. Budget discipline has been improved by strengthening the public financial system (PFM). The views of IMF staff regarding medium-term fiscal policy, the financial sector assessment program (FSAP), and tax measures have also been accepted by the authorities. Finally, the IMF staff appraisal also outlined. In this paper, recent developments in public external debt and public domestic debt are studied.